A percepção do professor sobre o uso de ferramentas nos ambientes virtuais de aprendizagem - Santos, Alexandre (2020)
The following study focuses on the teacher's perception of educational tools in virtual learning environments (VLE) within the scope of distance education. The interest in the theme arose as a result of the author's trajectory as a teacher, coordinator of the course in distance education and designer educational. In such environments, it is up to the teacher to monitor student activities, motivate learning, guide and provide the student with conditions for learning. The fundamental reflections that this work proposes are: a. Do the virtual environments made available to the teacher provide the educational tools necessary for teachers to adopt an effective dynamic? B. Do teachers participate in the choice of tools and teaching materials used in virtual learning environments? The methodology comprises the application of a Qualitative Descriptive Research, of the Multiple Case Study type, with educators who already work with DE (Distance education) platforms, and subsequent data analysis based on Bardin (1977) and Franco (2008): The evidences perceived in this panorama. For the contextual analysis and interpretation in this work, the use of the record of words repeated in the corpus of the interview denominated as Initial Category (Frequency of Words). The grouping of the initial categories gave rise to the intermediate categories. In this way, the initial and intermediate categories presented benefit the construction of the final categories. Survey of the state of the art of the use of tools in digital environments of learning and pre-analysis. The interviews, transcribed in full. Although each interview included different environments / platforms: Canvas, Teleduc, Blackboard, Moodle, the five interviews end up showing the perception of the interviewed teachers about the use of educational tools in VLE specifically in the Institutions where they work or have worked